What explains the productivity decline in manufacturing in the nineties in India? - Saon Ray (Indian Council for Research on International Economic Relations (ICRIER), 2014)
This paper uses the data envelopment analysis (DEA) based Malmquist productivity index to estimate total factor productivity growth (TFPG), technical change, and efficiency change for a panel of firms during the period 1991 to 2001 in 26 Indian manufacturing industries. The paper then analyses the factors explaining productivity growth, technical change and efficiency change using a Tobit regression for each industry. The results reveal that TFPG declined for all the sectors during the period. The most significant factor affecting efficiency change, technical change and productivity growth is RD intensity, either recurring or capital: this variable is significant in sixteen industries. Vintage of capital is significant in eight of the industries. Exports intensity and imports of capital intensity are significant in four industries.
Keywords: D24; O47; 330; productivity; efficiency; technical change